Detection strategies for the first supernovae with JWST. Issue 2 (14th June 2018) - Hartwig, Tilman; Bromm, Volker; Loeb, Abraham
ABSTRACT: Pair-instability supernovae (PISNe) are very luminous explosions of massive, low-metallicity stars. They can potentially be observed out to high redshifts due to their high explosion energies, thus providing a probe of the Universe prior to reionization. The near-infrared camera (NIRCam) on board the James Webb Space Telescope is ideally suited for detecting their redshifted ultraviolet emission. We calculate the photometric signature of high-redshift PISNe and derive the optimal detection strategy for identifying their prompt emission and possible afterglow. We differentiate between PISNe and other sources that could have a similar photometric signature, such as active galactic nuclei or high-redshift galaxies. We demonstrate that the optimal strategy, which maximizes the visibility time of the PISN light curve per invested exposure time, consists of the two wide-band filters F200W and F356W with an exposure time of 600 s. For such exposures, we expect one PISN at $z$ ≲ 7.5 per at least 50000 different field of view, which can be accomplished with parallel observations and an extensive archival search. The PISN afterglow, caused by nebular emission and reverberation, is very faint and requires unfeasibly long exposure times to be uniquely identified. However, this afterglow would be visible for several hundred years, about two orders of magnitude longer than the prompt emission, rendering PISNe promising targets for future, even more powerful telescopes.